2003
DOI: 10.1128/aem.69.1.358-366.2003
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Active-Form Streptoverticillium mobaraense Transglutaminase by Corynebacterium glutamicum : Processing of the Pro-Transglutaminase by a Cosecreted Subtilisin-Like Protease from Streptomyces albogriseolus

Abstract: The transglutaminase secreted by Streptoverticillium mobaraense is a useful enzyme in the food industry. A fragment of transglutaminase was secreted by Corynebacterium glutamicum when it was coupled on a plasmid to the promoter and signal peptide of a cell surface protein from C. glutamicum. We analyzed the signal peptide and the pro-domain of the transglutaminase gene and found that the signal peptide consists of 31 amino acid residues and the pro-domain consists of 45 residues. When the pro-domain of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
81
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(82 citation statements)
references
References 35 publications
1
81
0
Order By: Relevance
“…As a result, we derived a C. boidinii strain secreting a high amount of active TGase in the medium (about 90 mg/l), whose productivity was 20 times higher than that of the original strain and comparable to the level recently developed with a Corynebacterium expression system. 9) Since active TGase can be produced directly when the propeptide is coexpressed, neither simultaneous expression of exogenous protease nor refolding of the protein is necessary in the yeast expression system. Similar propeptide coexpression did not yield an active enzyme in the bacterial expression systems (data not shown), so the methylotrophic yeast expression system appears to be superior in this respect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, we derived a C. boidinii strain secreting a high amount of active TGase in the medium (about 90 mg/l), whose productivity was 20 times higher than that of the original strain and comparable to the level recently developed with a Corynebacterium expression system. 9) Since active TGase can be produced directly when the propeptide is coexpressed, neither simultaneous expression of exogenous protease nor refolding of the protein is necessary in the yeast expression system. Similar propeptide coexpression did not yield an active enzyme in the bacterial expression systems (data not shown), so the methylotrophic yeast expression system appears to be superior in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] The gene contains a 1,221-nucleotide open reading frame encoding a 407-amino acid protein, corresponding to the predicted pre-peptide of 31 amino acids, the pro-peptide of 45 amino acids, and the mature TGase of 331 amino acids. The pro-peptide inhibits enzyme activity and also increases enzyme thermostability, 8) but it is not necessary for catalytic activity.…”
mentioning
confidence: 99%
“…However, there had been only few reports concerning heterologous protein secretion in C. glutamicum. Recently, in many studies it has being demonstrated that Streptomyces mobaraensis transglutaminase (Date et al, 2004;Kikuchi et al, 2003) another enzyme used in the food industry, and human epidermal growth factor can be efficiently secreted in active form by C. glutamicum; so this strain is a potential host for industrial-scale protein production. In addition, the Tat pathway in C. glutamicum has been demonstrated to specifically mediate the secretion of Arthrobacter globiformis isomaltodextranase and green fluorescent protein (GFP) carrying an E. coli TorA signal peptide.…”
Section: Secretion By C Glutamicum Of Heterologous Proteinsmentioning
confidence: 99%
“…cinnamoneum (Duran et al, 1998), Streptoverticillium mobaraense (Kikuchi et al, 2003), Streptoverticillium ladakanum (Tellez-Luis et al, 2004), Streptomyces netropsis (Yu et al, 2008), and Streptoverticillium hygroscopicus (Aidaroos et al, 2011). It has also been reported to be found in Bacillus subtilis spores (Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%